2001
DOI: 10.1105/tpc.13.5.1179
|View full text |Cite
|
Sign up to set email alerts
|

Small Changes in the Regulation of One Arabidopsis Profilin Isovariant, PRF1, Alter Seedling Development

Abstract: Profilin (PRF) is a low-molecular-weight actin binding protein encoded by a diverse gene family in plants. Arabidopsis PRF1 transcripts are moderately well expressed in all vegetative organs. A regulatory mutant in PRF1 , prf1-1 , was isolated from a library of T-DNA insertions. The insertion disrupted the promoter region of PRF1 100 bp upstream from the transcriptional start site. Although steady state levels of PRF1 transcripts appeared normal in mature prf1-1 plants, the levels in young seedlings were only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 61 publications
(33 reference statements)
1
41
0
Order By: Relevance
“…Phenotypes observed included reduced cell expansion and shorter swollen roots and root hairs (Ramachandran et al, 2000). However, another study analyzed a T-DNA insertion in the most highly expressed profilin gene during seedling formation in Arabidopsis, which also reduced profilin levels by approximately twofold during germination, and this study observed an increase in cell expansion (McKinney et al, 2001).…”
Section: Introductionmentioning
confidence: 95%
“…Phenotypes observed included reduced cell expansion and shorter swollen roots and root hairs (Ramachandran et al, 2000). However, another study analyzed a T-DNA insertion in the most highly expressed profilin gene during seedling formation in Arabidopsis, which also reduced profilin levels by approximately twofold during germination, and this study observed an increase in cell expansion (McKinney et al, 2001).…”
Section: Introductionmentioning
confidence: 95%
“…It is likely that profilins have a similar role in formin-mediated actin polymerization in plant cells. Suppression of profilin gene expression affects cell growth, morphogenesis, and seedling growth, highlighting the important physiological function of profilin-mediated actin dynamics (Ramachandran et al, 2000;McKinney et al, 2001).…”
Section: Actin and Its Regulatory Proteinsmentioning
confidence: 99%
“…With the exception of AIP1 (Ketelaar et al, 2004a), most plant ABP mutants and suppression constructs affect the morphogenesis of only a variable subset of cell types. The tissue-specific nature of formin phenotypes (Deeks et al, 2005;Ingouff et al, 2005;Yi et al, 2005) and profilin (McKinney et al, 2001) can be considered to be a symptom of large gene families with the potential for genetic redundancy, but the relatively mild phenotypes of components of the Arp2/3 complex together with the unexpectedly severe Arabidopsis AIP1 phenotype suggests that plants place functional emphasis upon individual classes of ABPs in a pattern that differs from animals and fungi. Here, we show that the Arabidopsis homologue of CAP (CAP1) is essential for the development of multiple cell types and that null mutant phenotypes of these tissues correlate with actin organisational defects.…”
Section: Introductionmentioning
confidence: 99%